Elementa Theologiae Dogmaticae - Schouppe, Fancisci Xaverii (Gabriel Beauchesne et Cie, Editeurs, 1905)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage